2013
DOI: 10.1016/j.bbamem.2013.07.019
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the CD3 ζζ transmembrane dimer in POPC and raft-like lipid bilayer: A molecular dynamics study

Abstract: Plasma membrane lipids significantly affect assembly and activity of many signaling networks. The present work is aimed at analyzing, by molecular dynamics simulations, the structure and dynamics of the CD3 ζζ dimer in palmitoyl-oleoyl-phosphatidylcholine bilayer (POPC) and in POPC/cholesterol/sphingomyelin bilayer, which resembles the raft membrane microdomain supposed to be the site of the signal transducing machinery. Both POPC and raft-like environment produce significant alterations in structure and flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…These studies showed consistently that the extracellular CD3 domains are located underneath the TCR␣␤ chains (10 -12) but disagreed on proposed docking sites of the CD3 subunits to TCR␣␤ (11,12). Although the conformation of the small extracellular portion (9 residues) of is not known, the association of the helical transmembrane segments of 2 in micelles was determined by NMR (13) and refined in molecular dynamics simulations within a lipid bilayer (14,15). A model for the assembly of all eight transmembrane domains in the intact TCR complex has been proposed based on charge-pairing interactions within the bilayer (16).…”
Section: Interactions Between Lipid Bilayers and The Membrane-proximamentioning
confidence: 99%
“…These studies showed consistently that the extracellular CD3 domains are located underneath the TCR␣␤ chains (10 -12) but disagreed on proposed docking sites of the CD3 subunits to TCR␣␤ (11,12). Although the conformation of the small extracellular portion (9 residues) of is not known, the association of the helical transmembrane segments of 2 in micelles was determined by NMR (13) and refined in molecular dynamics simulations within a lipid bilayer (14,15). A model for the assembly of all eight transmembrane domains in the intact TCR complex has been proposed based on charge-pairing interactions within the bilayer (16).…”
Section: Interactions Between Lipid Bilayers and The Membrane-proximamentioning
confidence: 99%
“…Streptavidin-binding peptide (SBP)-tagged CD16A was cotranslated with either HA-tagged FceR1γ or HA-CD247 in the presence of ER-derived microsomes and 35 S-labeled methionine/cysteine, and then complex formation was quantitated in coimmunoprecipitation experiments (Fig. 1C and Fig.…”
Section: Cd16amentioning
confidence: 99%
“…Indeed, changes in the tilt angle of a transmembrane domain as well as changes in the NMR structure between pure lipid and raft-like bilayers have been reported for other membrane receptors [93,94]. The simulations presented here support the studies that suggest the membrane composition heavily influences the structure and behaviour of proteins embedded in the membrane.…”
Section: 7supporting
confidence: 76%